The impact of company trustworthiness on the success of cause-related marketing programs - İşcioğlu, Tutku Eker. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
For the past two decades increasing efforts have been given to investigating the influence of cause-related marketing (CRM) activities on consumers‟ attitudes and behaviors. Because consumers may react differently to companies that operate in the same industry with similar CRM applications, the understanding of the requirements of a successful CRM application is crucial. This study is aimed at examining two of these requirements that have been given only slight attention as influences on a successful CRM application in terms of purchase intent and company image. These are “company trustworthiness” and “the type of CRM campaign” (strategic and tactical). The proposed model is tested with an experimental design; and the analyses were conducted by MANCOVA and Repeated Measures MANCOVA. The findings do not support all of the hypothesized relationships, because a significant contribution by the influences was realized for the company image but not for the purchase intent. As the findings reveal, a highly trusted company that applies a CRM campaign has a better company image than a less trusted company. In addition, following a strategic CRM campaign creates a better company image than following a tactical one. The comparison of the company image before a CRM was applied with the image after it was applied revealed that it was only the type of CRM application that exerted a positive impact on the company image improvement. Interestingly, however, using a tactical CRM resulted in a more positive improvement in the company image than using a strategic CRM. The study ends with the implications for managers, academicians, and for further research.
Keywords: Marketing.